A Simplified Model for Flagellar Motion - Meinerz, Kelsey; Karkheck, John (Proceedings of the Wisconsin Space Conference, 2012)
Many bacteria use long, thin appendages called Flagella to propel them forward. Examples of bacteria which use these are Escherichia coli and Salmonella typhimurium. A rotary motor within the cell causes the flagellum to spin, which then propels the bacterium through its fluid environment. This is a complex process, especially for a single-celled organism. In order to better understand how this process works, we have created and tested a model for flagellar motion using springs in different fluids. Quantifying the propulsive force is an important goal, not only for relating it to bacterial motion, but also for potential applications in low gravity environments.Â